(untitled) (Proceedings of International Conference on Special Education, 2015)
An education programme for special needs children called “Program Khas Lestari Pendidikan” in National Primary Special Education School of Selangor is an innovation to outburst District Education Office of Petaling Perdana. The main purpose is to increase the school’s band from Band 6 (the lowest band in the district) to a higher band. This programme was planned carefully which was carried out for a nine-month period (Mac - November) and involved all School Improvement Partners Plus (SIP+) and School Improvement Specialist Coaches Plus (SISC+). The teachers were coached collectively and individually. Group programmes consisted of four series which focused on pedagogy, motivation and exposure on answering techniques examination questions of the National Primary Examination. The individual guidance was given once a month (March – September) in a classroom after teaching and learning had taken place. The program results showed a success rate in the aspect of quality improvement and teachers motivation. Sharing of experience from SISC+ on mathematic subject while carrying out “Program Khas Lestari Pendidikan” will give a valuable perspective and examples of the best practices to uphold the quality of teachers teaching and learning in the special needs schools.